2019
DOI: 10.2147/lra.s138537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anesthetic techniques: focus on transversus abdominis plane (TAP) blocks</p>

Abstract: Transverse abdominis plane (TAP) blocks, over the past decade, have emerged as a reliable tool in multimodal analgesia. Although they block only the somatic component of pain, studies have still revealed a consistent benefit in the first 24–48 hours after surgery in terms of pain scores and overall opioid consumption. The safety and dependability has increased with ultrasound usage. The aim of this review is to help the reader appreciate the applied anatomy required for a TAP block and its congeners, to standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…A number of authors have confirmed the safety of the postoperative infusion of lidocaine in doses ranging from 3,200mg to 6,000mg over a 48 hour period. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the past few years, the use of interfacial plane blocks has been more and more advocated, 20 including erector spinae plane blocks (ESPB) for thoracic surgery, [21][22][23][24][25] pectoralis and serratus blocks for breast surgery [26][27][28][29] and quadratus lumborum (QL) blocks for abdominal surgery, 30 Intravenous lidocaine (IV lido) infusions have been demonstrated to be an effective technique for postoperative analgesia in several different types of surgery, including abdominal, [31][32][33][34] thoracic, 35,36 and spine. 37,38 We hypothesized that SNBs followed by IV lido would be as effective as CNBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have confirmed the safety of the postoperative infusion of lidocaine in doses ranging from 3,200mg to 6,000mg over a 48 hour period. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the past few years, the use of interfacial plane blocks has been more and more advocated, 20 including erector spinae plane blocks (ESPB) for thoracic surgery, [21][22][23][24][25] pectoralis and serratus blocks for breast surgery [26][27][28][29] and quadratus lumborum (QL) blocks for abdominal surgery, 30 Intravenous lidocaine (IV lido) infusions have been demonstrated to be an effective technique for postoperative analgesia in several different types of surgery, including abdominal, [31][32][33][34] thoracic, 35,36 and spine. 37,38 We hypothesized that SNBs followed by IV lido would be as effective as CNBs.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the use of interfacial plane blocks has been more and more advocated, 20 including erector spinae plane blocks (ESPB) for thoracic surgery, 21-25 pectoralis and serratus blocks for breast surgery 26-29 and quadratus lumborum (QL) blocks for abdominal surgery, 30…”
Section: Introductionmentioning
confidence: 99%
“…When TEA is contraindicated, such as patient refusal, coagulation abnormalities, elevated intracranial pressure, and infection over the Tuohy needle insertion site, IV-PCA appears to be a reasonable alternative for pain control [ 25 ]. Nonetheless, opioid is often associated with adverse drug events (ADEs), including nausea, vomiting, delayed return of urinary and bowel function, over-sedation, respiratory depression, and exacerbation of hepatic encephalopathy [ 26 , 27 ], which becomes significant postoperatively when opioid metabolism may be impaired in correlation with the size of liver resection [ 28 ]. Optimal pain control without severe ADEs, therefore, is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…These blocks appear promising as analgesia is achieved while reducing opioid requirements. Patients may be able to have improved respiratory function leading to a shorter length of hospital stay and better satisfaction of the patients [ 26 , 27 , 29 , 30 , 31 , 32 , 33 ]. Generally, an open hepatectomy incision requires dermatome coverage from approximately T6 to T10, which can be covered by bilateral TAP blocks or left-sided rectus sheath block in addition to a right-sided TAP block [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transversus abdominis plane block (TAP block) which was described by Rafi et al in 2001, is a regional anesthesia technique that requires administration of local anesthetic solution below the fascia between the transversus abdominis muscle and internal oblique muscle of the anterior abdominal wall. [1][2][3][4] The benefits of TAP block are analgesia without sympathetic blockade and the consequent hypotension or bradycardia, unlike in neuraxial block; also, opioid-induced pruritus, nausea, and vomiting are generally not observed with TAP block. [5][6][7] The technical difficulty with ultrasoundguided TAP block and a dearth of time, discourage to perform the block; therefore, we designed this study to ascertain the efficacy of double pop blind TAP block, which can be delivered even in a resource-poor hospital set up.…”
Section: Introductionmentioning
confidence: 99%